Practical strategies for teaching K-12 social studies in inclusive classrooms - Lintner, Timothy; Schweder, Windy (Emerald Publishing Limited : Information Age Publishing, 2011)
With the national push towards inclusion, more students with disabilities are being placed in general education settings. Furthermore, when placed, more students with disabilities are entering social studies classrooms than any other content area. Classroom teachers are being asked to "reach and teach" all students, often with little support. There are numerous texts on the teaching of social studies, an equal number on teaching students with disabilities. Blending best practice in social studies and special education instruction, this book provides both pre - and in-service educators simple, practical strategies that support the creation of engaging, relevant, and appropriate social studies opportunities for all students.Though the strategies presented are useful for all students, they are particularly beneficial for students with disabilities. From Universal Design for Learning, mnemonics, graphic organizers, and big ideas, to co-teaching, screen readers and the Virtual History Museum, this book offers hands-on, practical ideas general educators can use when teaching K-12 social studies in inclusive classrooms.
Keywords: Social sciences -- Study and teaching (Elementary) -- United States.; Social sciences -- Study and teaching (Secondary) -- United States.; Inclusive education.; Education -- Schools -- Levels -- Elementary.; Primary and middle schools.; elektronické knihy; electronic books